Calcium, zinc, and vitamin D in breast milk: a systematic review and meta-analysis - Magali Rios-Leyvraz; Qisi Yao (International Breastfeeding Journal, 2023)
Abstract Background Global estimates of calcium, zinc and vitamin D content in breastmilk are lacking. The objective of this systematic review was to determine the calcium, zinc, and vitamin D content in breast milk. Methods A systematic search of the online databases Embase, MEDLINE, and CENTRAL was conducted in November 2022 and complemented by searches of the African Journals Online database and the LILACS database, and reference lists. Studies reporting the calcium, zinc and vitamin D content in breast milk of apparently healthy mothers and infants were included. Random effects meta-analyses were conducted. The effect of influencing factors were investigated with sub-group analyses and meta-regressions. Results A total of 154 studies reporting on breast milk calcium were identified, with a mean calcium concentration in breast milk of 261 mg/L (95% CI: 238, 284). Calcium concentration was influenced by maternal health and decreased linearly over the duration of lactation. Calcium concentration at a specific time during lactation could be estimated with the equation: calcium concentration [mg/L] = 282 – 0.2331 ✕ number of days since birth. A total of 242 studies reporting on breast milk zinc were identified, with a mean zinc concentration of 2.57 mg/L (95% CI: 2.50, 2.65). Zinc concentration was influenced by several factors, such as maternal age, gestational age, and maternal diet. Zinc concentration started high in the first weeks post-partum followed by a rapid decrease over the first months. Zinc concentration at a specific time during lactation could be estimated with the equation: zinc concentration [mg/L] = 6 + 0.0005 ✕ days – 2.0266 ✕ log(days). A total of 43 studies reporting on breast milk vitamin D were identified, with a mean total antirachitic activity of breast milk of 58 IU/L (95% CI: 45, 70), which consisted mostly of 25OHD3, and smaller amounts of vitamin D3, 25OHD2 and vitamin D2. Vitamin D concentration showed wide variations between studies and was influenced by vitamin D supplementation, continent and season. Conclusions This review provides global estimates of calcium, zinc and vitamin D content in breast milk, as well as indications on changes over time and depending on influencing factors.